Optimization and analysis of Machined surface on synthesized cobalt – Chromium composite. (2022) - Raguraman, D.; Vinoth, R.; Kesavaraj, K.; Sathish, S.; Kalil Rahiman, M.; Revathy, R.; Naga Raju, D.S.; Ram, S.
Highlights: Topography of machined surface is played an essential role in material processing and manufacturing methods. The present article is used to analysis the spark erosion machined surface of synthesized silicon carbide based cobalt chromium composite. It was observed that the superior substance properties were attained from the composition of cobalt and chromium. Scanning force microscopy (SFM) is utilized to analysis the machined topography. It was employed to examine the machined surface topography. The machining characteristics were analyzed through various input and output constraints. Taguchi method was employed to found the optimal removal of material. It was concluded that voltage was created the largest effect on removal of materials. Abstract: Topography of machined surface is played an essential role in material processing and manufacturing methods. The present article is used to analysis the spark erosion machined surface of synthesized silicon carbide based cobalt chromium composite. It was observed that the superior substance properties were attained from the composition of cobalt and chromium. Scanning force microscopy (SFM) is utilized to analysis the machined topography. It was employed to examine the machined surface topography. The machining characteristics were analyzed through various input and output constraints. Taguchi method was employed to found the optimal removal of material. It was concluded that voltage was created the largest effect on removal of materials.